2015
DOI: 10.15740/has/tajh/10.2/222-231
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effect of growth regulator and vermicompost on growth and yield of different cultivars of strawberry (Fragaria x ananassa Duch)

Abstract: :The present investigation was carried out at the Horticulture Research Center, of the SardarVallabhbhai Patel University of Agriculture and Technology, Meerut during 2013-2014.The maximum number of fruits (20.85) were recorded in the variety Chandler which was significantly superior to the rest of the varieties and followed by Gorella,Selva and Confictura.The maximum fruit yield per plant (385.57g) was recorded in the variety Chandler which was superior to the rest of the varieties and was followed by Selva, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Total soluble solids Total soluble solids readings showed that the maximum amount was noted in strawberry fruits sprayed with T 2 (GA 3 @ 100 ppm) (13.21%), while the minimum amount was observed in T 7 [Control (Only water)] (7.56%) (Table 2). Effect of growth regulators on sugars of strawberry is highly dependent on concentration and chemical composition of plant growth regulators (Jamal Uddin et al, 2012;Rajbhar et al, 2015). In present study, GA 3 @ 100 ppm has been reported to be the most effective among treatments in terms of total soluble solids of strawberry which might be due to its right concentration which helped in increasing the total soluble solids of strawberry.…”
Section: Postharvest Quality Parametersmentioning
confidence: 50%
“…Total soluble solids Total soluble solids readings showed that the maximum amount was noted in strawberry fruits sprayed with T 2 (GA 3 @ 100 ppm) (13.21%), while the minimum amount was observed in T 7 [Control (Only water)] (7.56%) (Table 2). Effect of growth regulators on sugars of strawberry is highly dependent on concentration and chemical composition of plant growth regulators (Jamal Uddin et al, 2012;Rajbhar et al, 2015). In present study, GA 3 @ 100 ppm has been reported to be the most effective among treatments in terms of total soluble solids of strawberry which might be due to its right concentration which helped in increasing the total soluble solids of strawberry.…”
Section: Postharvest Quality Parametersmentioning
confidence: 50%
“…Dual inoculation with 75% N and 100ppm BA gives maximum Yield and fruit set was maximum in combination of GA3 100ppm + 50% N + azotobactor + azospirillium application. Rajbhar et al, (2015) found that GA3 100ppm + vermicompost @100q/ha resulted more TSS (10.68 ºBrix) in strawberry var. Douglas.…”
Section: Floweing Fruit Set and Yield Parametermentioning
confidence: 92%
“…Sujata. Rajbhar et al, (2015) reported that GA3 (100 ppm) resulted higher yield in Chandler cv. of strawberry.…”
Section: Growth Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Hassan (2015) and Saha et al (2019) were reported the better vegetative growth of plants and number of leaves in strawberry with the use organic and in-organic fertilizers. Rajbhar et al, 2015 was also reported same while working on strawberry.…”
Section: Growth Parametersmentioning
confidence: 69%